Prevention and Treatment of Diabetic Foot Syndrome in Patients with Diabetes in Andijan Region - R.T.Uktamov; Sh.K.Yusupova; G.M.Bektasheva (Global Scientific Publishing, 2023)
Diabetes mellitus (DM) is one of the leading causes of general morbidity, disability, and mortality in the population, including those of working age. The social significance of DM is determined by its complications. Diabetic foot syndrome (DFS) occupies a special place among infectious and inflammatory diseases in patients with DM 2 (DM 2). According to the algorithms of specialized medical care for patients with diabetes, “The diabetic foot syndrome combines pathological changes in the peripheral nervous system, arterial and microcirculatory channels, and the osteoarticular apparatus of the foot, which pose an immediate threat or the development of ulcerative necrotic processes and gangrene of the foot.” SDS requires an integrated approach on the part of many specialists, since the lesion of the lower extremities is at the junction of several medical disciplines: therapeutic and surgical. With untimely diagnosis and the absence of correct pharmacotherapy at the very beginning of the development of complications, DFS progresses rapidly, gangrene of the lower limb develops, which can result in its amputation with subsequent disability of the patient - the most terrible consequence of DFS. According to statistics, up to 90% of patients are hospitalized in surgical hospitals on an emergency basis at the stage of irreversible clinical and morphological changes, about 85-90% of cases end in amputation of the lower limb
Keywords: antibiotic therapy; complete blood count; prothrombin time